A stir bar sorptive extraction device coupled with a gas chromatography flame ionization detector for the determination of abused prescription drugs in lean cocktail samples. Issue 26 (14th June 2022) - Nualdee, Kamonwan; Buain, Ratchaneekorn; Janchawee, Benjamas; Sukree, Warakorn; Thammakhet-Buranachai, Chongdee; Kanatharana, Proespichaya; Chaisiwamongkhol, Korbua; Prutipanlai, Sathaporn; Phonchai, Apichai
Abstract : This work presents an in-house developed stir bar sorptive extraction (SBSE) device with an XAD-2 adsorbent followed by analysis using GC-FID for the extraction and determination of the five main abused prescription drugs in lean cocktail samples. Abstract : A lean cocktail is a mixed drink for the non-medical use of prescription medications that has emerged in recent years as a drug of abuse and is related to drug-facilitated crimes. The determination of active ingredients in a lean cocktail is necessary for forensic investigations. This work presents an in-house developed stir bar sorptive extraction (SBSE) device with an XAD-2 adsorbent followed by analysis using GC-FID for the extraction and determination of the five main abused prescription drugs (diphenhydramine, tramadol, chlorpheniramine, dextromethorphan and promethazine) in lean cocktail samples. Under optimized conditions, the developed method provided linearity for 1.0–250 μg mL −1 of each of the five abused prescription drugs. The limits of detection and limits of quantitation were in the respective ranges of 0.25–0.5 μg mL −1 and 1.0–1.5 μg mL −1 . The percentage of extraction was 85.0–94.9%. The intra-day and inter-day precisions were 1.2–14.4% RSD and 1.4–15.8% RSD, respectively. Good relative recoveries in the range of 86.7–110.3% and 88.5–107.9% were obtained when the proposed method was applied for extraction and analysis of abused prescription drugs in five lean cocktail samples. The developed method can be a useful tool for measuring the levels of abused prescription drugs in a lean cocktail and the data could also be used as evidence in a forensic investigation.